Five decades of research in healthcare pricing: future directions for academia and policymakers. (19th March 2019) - Pandey, Neeraj; Raina, Abhinav
While a vast body of research literature is dedicated to healthcare and its related aspects, few studies have synthesised the data available on the crucial aspect of healthcare pricing. This work uses the techniques of natural language processing (NLP) and Aduna clustering to present a comprehensive review of five decades (1970-2017) of research on healthcare pricing. The study maps the stages of evolution in healthcare pricing research with the help of parameters such as research themes, prominent authors and journals, keywords, institutions and countries where these studies were conducted. Findings highlight the gaps in the extant literature, which present valuable opportunities for academia and policymakers in the field of healthcare pricing.